Preoperative Cardiac Variables of Diastolic Dysfunction and Clinical Outcomes in Lung Transplant Recipients. (12th September 2013) - Yadlapati, Ajay; Lynch, Joseph P.; Saggar, Rajan; Ross, David; Belperio, John A.; Weigt, Stephen; Ardehali, Abbas; Grogan, Tristan; Yang, Eric H.; Aboulhosn, Jamil
Abstract : Background . Orthotopic lung transplantation is now widely performed in patients with advanced lung disease. Patients with moderate or severe ventricular systolic dysfunction are typically excluded from lung transplantation; however, there is a paucity of data regarding the prognostic significance of abnormal left ventricular diastolic function and elevated pretransplant pulmonary pressures. Methods . We reviewed the characteristics of 111 patients who underwent bilateral and unilateral lung transplants from 200 to 2009 in order to evaluate the prognostic significance of preoperative markers of diastolic function, including invasively measured pulmonary capillary wedge pressure (PCWP) and echocardiographic variables of diastolic dysfunction including mitralA > E andA ′ > E ′ . Results . Out of 111 patients, 62 were male (56%) and average age was 54.0 ± 10.5 years. Traditional echocardiographic Doppler variables of abnormal diastolic function, includingA ′ > E ′ andA > E, did not predict adverse events (P = 0.49 ). Mildly elevated pretransplant PCWP (16–20 mmHg) and moderately/severely elevated PCWP (>20 mmHg) were not associated with adverse clinical events after transplant (P = 0.30 ). Additionally, all clinical endpoints did not show any statistical significance between the two groups. Conclusions . Pre-lung transplant invasive and echocardiographic findings of elevated pulmonary pressures and abnormal left ventricular diastolic function are not predictive of adverse posttransplant clinical events.